The Influence of Agricultural Land Use on the Drivers of Peri-Urban Settlement Formation in Highland Landscapes: a Case Study in the Kayumas Village - Jehan Fakhirah; Renny Nurhasana (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The Peri-Urban as part of the urban spatial structure, plays a crucial role in creating urban space. In Situbondo, the characteristics of the Peri-Urban consist of mixed urban and peri-urban land use areas, with agriculture dominating the land use. One of the livelihoods in the Peri-Urban is agriculture. Variables in this study involve elements of settlement morphology, factors influencing the formation of morphology and agriculture, and various other indicators related to these variables. This paper aims to examine the characteristics of agriculture areas and identify factors influencing the formation of peri-urban settlements. This research can provide references to optimize land use in peri-urban settlements. In this study, the researcher employs both qualitative and quantitative methods. Data collection involves recording events that occur in the field during interviews and observations to obtain accurate and reliable research results. The data will be processed using SPSS and ArcGIS 10.8.2 to obtain relevant, supportive accurate, and comprehensive results. From the findings of this research, it is expected that peri-urban settlements require more attention to enhance the environment and public services. In response to the consumption-oriented needs of urban communities, Peri-Urban farmers have intensified the use of multifunctional land activities. However, not all multifunctional opportunities are fully developed, considering the farming activities conducted near the city. This can be an innovative characteristic of land use in the Situbondo Peri-Urban area, indicating that agriculture is a priority land use in the region by improving the quality of harmonious relationships between urban and peri-urban areas through agriculture activities